Endovascular treatment of symptomatic intracranial atherosclerotic disease - Hussain, Syed I. (Frontiers in Neurology, 2011)
Abstract: Symptomatic intracranial atherosclerotic disease (ICAD) is responsible for approximately 10% of all ischemic strokes in the United States. The risk of recurrent stroke may be as high as 35% in patient with critical stenosis greater than 70% in diameter narrowing. Recent advances in medical and endovascular therapy have placed ICAD at the forefront of clinical stroke research to optimize the best medical and endovascular approach to treat this important underlying stroke etiology. Analysis of symptomatic ICAD studies lead to the question that whether angioplasty and or stenting is a safe, suitable and efficacious therapeutic strategy in patients with critical stenoses that are deemed refractory to medical management. Most of the currently available data in support of angioplasty and or stenting in high risk patients with severe symptomatic ICAD is in the form of case series and randomized trial results of endovascular therapy versus medical treatment are awaited. This is a comprehensive review of the state of the art in the endovascular approach with angioplasty and or stenting of symptomatic intracranial atherosclerotic disease.